TNB-738, a biparatopic antibody, boosts intracellular NAD+ by inhibiting CD38 ecto-enzyme activity. Issue 1 (31st December 2022) - Ugamraj, Harshad S.; Dang, Kevin; Ouisse, Laure-Hélène; Buelow, Benjamin; Chini, Eduardo N.; Castello, Giulia; Allison, James; Clarke, Starlynn C; Davison, Laura M.; Buelow, Roland; Deng, Rong; Iyer, Suhasini; et al.
ABSTRACT: Cluster of differentiation 38 (CD38) is an ecto-enzyme expressed primarily on immune cells that metabolize nicotinamide adenine dinucleotide (NAD+) to adenosine diphosphate ribose or cyclic ADP-ribose and nicotinamide. Other substrates of CD38 include nicotinamide adenine dinucleotide phosphate and nicotinamide mononucleotide, a critical NAD+ precursor in the salvage pathway. NAD+ is an important coenzyme involved in several metabolic pathways and is a required cofactor for the function of sirtuins (SIRTs) and poly (adenosine diphosphate-ribose) polymerases. Declines in NAD+ levels are associated with metabolic and inflammatory diseases, aging, and neurodegenerative disorders. To inhibit CD38 enzyme activity and boost NAD+ levels, we developed TNB-738, an anti-CD38 biparatopic antibody that pairs two non-competing heavy chain-only antibodies in a bispecific format. By simultaneously binding two distinct epitopes on CD38, TNB-738 potently inhibited its enzymatic activity, which in turn boosted intracellular NAD+ levels and SIRT activities. Due to its silenced IgG4 Fc, TNB-738 did not deplete CD38-expressing cells, in contrast to the clinically available anti-CD38 antibodies, daratumumab, and isatuximab. TNB-738 offers numerous advantages compared to other NAD-boosting therapeutics, including small molecules, and supplements, due to its long half-life, specificity, safety profile, and activity. Overall, TNB-738 represents a novel treatment with broad therapeutic potential for metabolic and inflammatory diseases associated with NAD+ deficiencies. Abbreviations: 7-AAD: 7-aminoactinomycin D; ADCC: antibody dependent cell-mediated cytotoxicity; ADCP: antibody dependent cell-mediated phagocytosis; ADPR: adenosine diphosphate ribose; APC: allophycocyanin; cADPR: cyclic ADP-ribose; cDNA: complementary DNA; BSA: bovine serum albumin; CD38: cluster of differentiation 38; CDC: complement dependent cytotoxicity; CFA: Freund's complete adjuvant; CHO: Chinese hamster ovary; CCP4: collaborative computational project, number 4; COOT: crystallographic object-oriented toolkit; DAPI: 4′, 6-diamidino-2-phenylindole; DNA: deoxyribonucleic acid; DSC: differential scanning calorimetry; 3D: three dimensional; εNAD+: nicotinamide 1, N6 -ethenoadenine dinucleotide; ECD: extracellular domain; EGF: epidermal growth factor; FACS: fluorescence activated cell sorting; FcγR: Fc gamma receptors; FITC: fluorescein isothiocyanate; HEK: human embryonic kidney; HEPES: 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid; IgG: immunoglobulin; IFA: incomplete Freund's adjuvant; IFNγ: Interferon gamma; KB: kinetic buffer; kDa: kilodalton; KEGG: kyoto encyclopedia of genes and genomes; LDH: lactate dehydrogenase; M: molar; mM: millimolar; MFI: mean fluorescent intensity; NA: nicotinic acid; NAD: nicotinamide adenine dinucleotide; NADP: nicotinamide adenine dinucleotide phosphate; NAM: nicotinamide; NGS: next-generation sequencing; NHS/EDC: N-Hydroxysuccinimide/ ethyl (dimethylamino propyl) carbodiimide; Ni-NTA: nickel-nitrilotriacetic acid; nL: nanoliter; NK: natural killer; NMN: nicotinamide mononucleotide; OD: optical density; PARP: poly (adenosine diphosphate-ribose) polymerase; PBS: phosphate-buffered saline; PBMC: peripheral blood mononuclear cell; PDB: protein data bank; PE: phycoerythrin; PISA: protein interfaces, surfaces, and assemblies: PK: pharmacokinetics; mol: picomolar; RNA: ribonucleic acid; RLU: relative luminescence units; rpm: rotations per minute; RU: resonance unit; SEC: size exclusion chromatography; SEM: standard error of the mean; SIRT: sirtuins; SPR: surface plasmon resonance; µg: microgram; µM: micromolar; µL: microliter